Tinjauan Hukum terhadap Generic Terms dalam Perlindungan Merek - Yemima Andria Hotmauli Simanjuntak; Jeane Nelje Saly (Syntax Corporation, 2023)
The development of trade activities in goods and services in Indonesia has increased quite significantly due to developments in information and transportation technology which have caused activities in the trade sector in the creation of works for goods and services to experience rapid development. One form of law protection called intellectual property rights, namely trademarks. Through this research, we will discuss legal reflections on general terms which are one of several conditions that are prohibited when submitting an application for trademark name registration. This research method uses a normative method with research specifications, namely analytical descriptive using a case approach that examines Verdict Number 85/Pdt.Sus-HKI/Merek/2022/PN. Niaga.Jkt.Pst. The aim of this research is to provide knowledge to the public who are prospective trademark registrants to know the criteria for brand names that can be registered or cannot be registered, in this case regarding brands that contain elements of generic terms. The conclusion proves that a generic term is a meaning that refers to a group of products or terms that are common among consumers or the public. Supposedly, brands registered using generic terms or general terms that are part of the public domain cannot pass or go through the substantive examination stage in the trademark examination process. This needs to be prevented because if the trademark application is granted, inquiries can give the trademark owner monopoly rights over the use of the trademark so that the trademark cannot compete effectively.